Analisis Strategi Pengembangan Usaha Melalui Diversifikasi Produk Pada Optik Princess Di Bandar Lampung - Iqsar, Muhammad; Miniawati, Tina (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study presents a business development strategy analysis for Optik Princess in Bandar Lampung. Through the SWOT, IFAS, and EFAS analysis approaches, we evaluated internal and external factors that could impact the company's performance. Findings indicate that Optik Princess possesses a good reputation and satisfactory customer service but faces limitations in product offerings and dependence on the local market. Opportunities for new service development, leveraging cutting-edge technology, and market expansion were identified as key strategies. Strategic conclusions involve responsiveness to external changes, ongoing innovation, and the strengthening of customer relations.